On estimations of the Taylor coefficients of functions from the class Kn(E) - Kirjackis, Eduardas (Lietuvos matematikos rinkinys, 2007)
In the article the estimations of the Taylor coefficients of functions from class Kn(E), formed by holomorphicin unit circle E = {|z|